Alignment Between Children's Numeracy Performance, the Kindergarten Common Core State Standards for Mathematics, and State-Level Early Learning Standards - Ellen C. Litkowski; Robert J. Duncan; Jessica A. R. Logan; David J. Purpura (SAGE Publishing, 2020)
The current study examined preschoolers' ( N = 801) age-related performance on one measure of verbal counting and two measures of cardinality ("how many" and "give n") aligned with the kindergarten Common Core State Standards for Mathematics (CCSSM) and included in the majority of states' early learning guidelines for mathematics. Children were grouped into five age categories (3, 3.5, 4, 4.5, 5, 5.5), and within-age-group average rates of correct responses for each item within these three measures were calculated. Results demonstrated that the majority of children were already successfully meeting the CCSSM standards for both cardinal number knowledge tasks (86.5% and 53.3%, respectively) prior to kindergarten entry but that only 18.9% of the children were meeting the standard for verbal counting. Findings indicate potential misalignment between children's existing capabilities and the CCSSM standards for cardinality and underscore the need to conduct large, nationally representative studies measuring children's abilities on items that more closely assess the specific mathematics skills included in the CCSSM and early learning guidelines.